Synthesis of Kenaf Cellulose Supported Highly Active Poly(amidoxime) Palladium Complex and Its Application as a Reusable Catalyst for Allylic Arylation reactions - Mandal, Bablu Hira; Sarkar, Shaheen M.; Lutfor, M. R.; Mohd Hasbi, Ab. Rahim (Universiti Malaysia Pahang, 2016)
A highly active kenaf cellulose supported poly(amidoxime) palladium catalyst was sythesized and the catalyst (65 mol ppm to 6.5 mol ppm) was found to promote efficiently allylic arylation of allylic ester with sodium tetraarylborates and arylboronic acids in ethanol at 60 °C temperature. Oustanding yields of the corresponding products as well as significant reusability of the catalyst were obtained. The total turnover number(TON) and frequency(TOF) were 144615 and 9641 h–1 respectively.